BRIDGING STRATEGY AND ITS IMPACT IN REINFORCEMENT SOCIAL CAPITAL - Baqer Khudair Al-Hadrawi; Ameer Rajeh Jawad (Scholars Digest Publishing, 2023)
In order to ascertain how these kinds of organizational connections can raise the level of social capital, the current study analyses a sample of university leaders at the University of Baghdad in Iraq to examine the relationship between the bridging approach and social capital. utilizing a descriptive analytical technique to accomplish its goals. The findings demonstrated a significant positive influence relationship between the bridging approach and social capital, where the bridging method promotes social cohesion and the greater the sense of community, the more successful the bridging strategy, The more social cohesion there is, the more engagement and cooperation there is, and the more social capital there is to grow and flourish.
Keywords: bridging strategy, social capital, University of Baghdad, Iraq.